Clinical Severity in Lesch-Nyhan Disease: the Role of Residual Enzyme and Compensatory Pathways - Fu, Rong (Mol Genet Metab, 2014)
Mutations in the HPRT1 gene, which encodes the purine salvage enzyme hypoxanthine-guanine phosphoribosyltransferase (HGprt), cause Lesch-Nyhan disease (LND) and more mildly affected Lesch-Nyhan variants. Prior studies have suggested a strong correlation between residual hypoxanthine recycling activity and disease severity. However, the relevance of guanine recycling and compensatory changes in the de novo synthesis of purines have received little attention. In the current studies, fibroblast cultures were established for 21 healthy controls and 36 patients with a broad spectrum of disease severity related to HGprt deficiency. We assessed hypoxanthine recycling, guanine recycling, steady-state purine pools, and de novo purine synthesis. There was a strong correlation between disease severity and either hypoxanthine or guanine recycling. Intracellular purines were normal in the HGprt-deficient fibroblasts, but purine wasting was evident as increased purine metabolites excreted from the cells. The normal intracellular purines in the HGprt-deficient fibroblasts was likely due in part to a compensatory increase in purine synthesis, as demonstrated by a significant increase in purinosomes. However, the increase in purine synthesis did not appear to correlate with disease severity. These results refine our understanding of the potential sources of phenotypic heterogeneity in LND and its variants.